Cutting Edge and Cutting Corners: Evolving Technology, Expanding Usership, and Responsive Solutions in a Museum Database. Issue 3 (August 2019) - Hansen, John S.
ABSTRACT: In the mid-1980s, the Anthropology Division of the American Museum of Natural History (AMNH) began the creation of digital resources as a means of collections access. Much of the database work was a secondary component of projects funded by outside grants and driven by new accountability mandates. The ongoing upgrading process was sporadic in its progress, but it still accomplished the primary goals of improved housing for collections and an exhaustive database. This paper discusses how the historical complications of the data, the scale of the database, its irregular schedule of funding, and deadline-driven projects resulted in inconsistency in data and difficulty in use. Although the examples provided will be specific to the AMNH Anthropology database, the circumstances and issues are common to many databases and the approaches presented broadly applicable. The discussion includes the practices used to mitigate the negative impact of these problems and the way the Division is positioning itself for the future, even as the database continues to provide unprecedented public and institutional access to and utility for the AMNH Anthropology collections. Abstract : A mediados de la década de 1980, la División de Antropología del Museo Americano de Historia Natural comenzó la creación de recursos digitales como medio de acceso a las colecciones. Gran parte del trabajo de base de datos era un componente secundario de los proyectos financiados por subvenciones externas e impulsado por nuevos mandatos de responsabilidad. El proceso de actualización en curso fue esporádico en su progreso, pero aún así logró los objetivos principales de mejoras al almacenamiento de colecciones y una exhaustiva base de datos. Este trabajo analiza cómo las complicaciones históricas de los datos, la escala de la base de datos, su calendario irregular de financiamiento y los proyectos impulsados por plazos resultaron en una inconsistencia en los datos y en la dificultad de uso. Aunque los ejemplos proporcionados serán específicos a la base de datos de antropología del AMNH, las circunstancias y los problemas son comunes para muchas bases de datos y los enfoques presentados son aplicables de manera general. La discusión incluye las prácticas utilizadas para mitigar el impacto negativo de estos problemas y cómo la División se está posicionando para el futuro, aun cuando la base de datos continúa brindando acceso y utilidad sin precedentes para las colecciones de Antropología de AMNH.